Serum immunoglobulin (IgG, IgM, IgA) and IgG subclass concentrations in healthy children: a study using nephelometric technique - Aksu, Güzide; Genel, Ferah; Koturoğlu, Güldane; Kurugöl, Zafer; Kütükçüler, Necil (The Turkish Journal of Pediatrics, 2006)
Immunoglobulin (Ig) G, IgM, IgA and IgG subclass (IgG1, IgG2, IgG3, IgG4) concentrations were determined in more than 500 healthy Turkish children using nephelometric technique. These parameters were thought to be highly varied for different ethnic groups because of environmental and genetic factors. Methodology used in previous studies has been reported to affect age-related normal values. Serum IgG, IgM, IgA and IgG1, IgG2, IgG3, IgG4 levels were measured in 510, 491, 486, 542, 511, 515, and 545 healthy children, respectively. According to their age, the patients were divided into 14 groups. In contrast to most of the previous studies, age-related normal values for IgG4 levels were also obtained. In conclusion, it has been suggested that our study as an example for Caucasians using nephelometric technique will supply useful information about age-related normal serum immunoglobulin and IgG subclass concentrations.